Coastal Degradation in Tanjung Uma, Batam City, Indonesia: A SWOT Analysis of Environmental Challenges and Opportunities - Suhardono, Sapta; Adicita, Yosef; Sari, Mega Mutiara; Tehupeiory, Aarce; Suryawan, I Wayan Koko (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
This research examines the escalating environmental degradation observed along the Tanjung Uma coastline, juxtaposing its unique challenges with the global narrative of declining coastal health. As a thriving marine ecosystem, Tanjung Uma has recently experienced considerable ecological decline, cascading effects on local biodiversity, community livelihoods, and socio-cultural dynamics. The study provides a granular understanding of the region's strengths, weaknesses, opportunities, and threats by combining a comprehensive literature review and a SWOT analysis. Findings highlight the dire state of the marine environment, driven by factors such as pollution, waste accumulation, and broader implications of climate change. However, the research also underscores the potential for regional cooperation, community engagement, and leveraging traditional knowledge as avenues for sustainable intervention. As a microcosm of global coastal challenges, Tanjung Uma's case offers insights that can inform broader strategies for marine conservation and community resilience.